Aplicação de metodologias ativas no ensino e aprendizagem de números racionais com questões da OBMEP - Junqueira, Juliana Roberta (2021)
This study aims to investigate the use of active methodologies in teaching and learning mathematics. For this study, the result of the work developed with questions from the OBMEP in the city of São Carlos-SP was observed (work that was presented as the Final Course Paper, in the Post-Graduate Course Lato Sensu: Teaching of Mathematics in High School - Matem @tica na Pr@tica) with the title - OBMEP Questions helping to learn the content of natural and rational numbers - and the work developed in the city of São João das Duas Pontes-SP at the José Brandini State School, a school belonging to the Board of Directors of Education – Region of Fernandópolis and which joined the group of schools belonging to the Integral Education Program (PEI) in 2020. Through the analysis of the external and internal evaluations of the José Brandini State School carried out at the beginning of the 2020 school year, the team of Natural Sciences and Mathematics under the guidance of the PCA (Area Coordinating Teacher) Juliana Roberta Junqueira noted that there is a large gap in skills related to the issue of numbers rational, in all years/series. Thus, in discussions in the Collective Pedagogical Work Classes by Area of Knowledge (ATPCA) meetings, all teachers began to investigate which objects of knowledge related to the topic of rational numbers were in greater gaps in each year/grade. From this study, the study of active methodologies began, what they are, and how they can contribute to improve the teaching and learning of students, thus, we began to investigate which active methodologies would be more viable to be applied in each year/series, seeking to overcome such weaknesses and recover such gaps. After defining the methodologies to be used, the teachers started working with the students, applying such methodologies and evaluating their use and the results produced every two months. This work began in February 2020 and is still being applied at school. Every two months, skills that are out of step and the best methodologies are studied in order to recover them. Unfortunately, we suffered from the suspension of classroom classes due to the COVID-19 pandemic that made us rethink the way to use such methodologies, even so we were able to observe that the use of such methodologies had a positive result in the teaching and learning of PEI E.E. José Brandini.